2021
DOI: 10.1111/febs.16226
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Hsp14 drives substrate shuttling between small heat shock proteins and thermosome: insights into a novel substrate transfer pathway

Abstract: Heat shock proteins maintain protein homeostasis and facilitate the survival of an organism under stress. Archaeal heat shock machinery usually consists of only sHsps, Hsp70, and Hsp60. Moreover, Hsp70 is absent in thermophilic and hyperthermophilic archaea. In the absence of Hsp70, how aggregating protein substrates are transferred to Hsp60 for refolding remains elusive. Here, we investigated the crosstalk in the heat shock response pathway of thermoacidophilic crenarchaeon Sulfolobus acidocaldarius. In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 98 publications
(212 reference statements)
0
9
0
Order By: Relevance
“…This phenomenon has been observed in Mycobacterium butanii , Pyrococuus furiosus, and also in Sulfolobus acidocaldarius ( Laksanalamai et al, 2006 ; Laksanalamai et al, 2009 ; Luo et al, 2009 ; Roy et al, 2021 ). It has been observed that excess addition of sHsp from Thermococcus sp .…”
Section: Different Functions Of Small Heat Shock Proteinsmentioning
confidence: 58%
See 4 more Smart Citations
“…This phenomenon has been observed in Mycobacterium butanii , Pyrococuus furiosus, and also in Sulfolobus acidocaldarius ( Laksanalamai et al, 2006 ; Laksanalamai et al, 2009 ; Luo et al, 2009 ; Roy et al, 2021 ). It has been observed that excess addition of sHsp from Thermococcus sp .…”
Section: Different Functions Of Small Heat Shock Proteinsmentioning
confidence: 58%
“…Furthermore, in hyperthermophilic and some thermophilic archaea, Hsp70 is also absent ( Usui et al, 2004 ). Interestingly, it has recently been demonstrated that in the absence of Hsp70, sHsps of these organisms could directly transfer the associated substrate protein to Hsp60 for refolding ( Laksanalamai et al, 2006 ; Laksanalamai et al, 2009 ; Roy et al, 2021 ). Studies have shown that Pyrococcus furiosus Hsp60 refolds heat-inactivated Taq polymerase five-fold more efficiently in the presence of sHsp ( Laksanalamai et al, 2006 ).…”
Section: Crosstalk Between Heat Shock Proteins and Substrate Transfermentioning
confidence: 99%
See 3 more Smart Citations